A drug-related Good Samaritan Law and calling emergency medical services for drug overdoses in a Canadian setting - Moallef, Soroush; Choi, JinCheol; Milloy, M.-J.; DeBeck, Kora; Kerr, Thomas; Hayashi, Kanna (Harm Reduction Journal, 2021)
Abstract Background People who use drugs (PWUD) are known to fear calling emergency medical services (EMS) for drug overdoses. In response, drug-related Good Samaritan Laws (GSLs) have been widely adopted in the USA and Canada to encourage bystanders to call emergency medical services (EMS) in the event of a drug overdose. However, the effect of GSLs on EMS-calling behaviours has been understudied. We sought to identify factors associated with EMS-calling, including the enactment of the Canadian GSL in May 2017, among PWUD in Vancouver, Canada, a setting with an ongoing overdose crisis. Methods Data were derived from three prospective cohort studies of PWUD in Vancouver in 2014–2018. Multivariable logistic regression was used to determine factors associated with EMS-calling among PWUD who witnessed an overdose event. An interrupted time series (ITS) analysis was employed to assess the impact of GSL on monthly prevalence of EMS-calling. Results Among 540 eligible participants, 321 (59%) were males and 284 (53%) reported calling EMS. In multivariable analysis, ever having administered naloxone three or more times (adjusted odds ratio [AOR] 2.00; 95% confidence interval [CI] 1.08–3.74) and residence in the Downtown Eastside (DTES) neighbourhood of Vancouver (AOR 1.96; 95% CI 1.23–3.13) were positively associated with EMS-calling, while living in a single occupancy hotel (SRO) was negatively associated with EMS-calling (AOR 0.51; 95% CI 0.30–0.86). The post-GSL enactment period was not associated with EMS-calling (AOR 0.81; 95% CI 0.52–1.25). The ITS found no significant difference in the monthly prevalence of EMS-calling between pre- and post-GSL enactment periods. Conclusion We observed EMS being called about half the time and the GSL did not appear to encourage EMS-calling. We also found that individuals living in SROs were less likely to call EMS, which raises concern given that fatal overdose cases are concentrated in SROs in our setting. The link between many naloxone administrations and EMS-calling could indicate that those with prior experience in responding to overdose events were more willing to call EMS. Increased efforts are warranted to ensure effective emergency responses for drug overdoses among PWUD.